Influence of Defect Size and Localization on the Engagement of Reverse Hill-Sachs Lesions. (March 2015) - Moroder, Philipp; Runer, Armin; Kraemer, Manuel; Fierlbeck, Johann; Niederberger, Alfred; Cotofana, Sebastian; Vasvari, Imre; Hettegger, Bernhard; Tauber, Mark; Hurschler, Christof; Resch, Herbert
Background: Reverse Hill-Sachs (RHS) lesions can cause recurrent posterior shoulder instability because of engagement with the posterior glenoid rim; however, the effect of defect size and localization have yet to be determined. Hypothesis: Both size and localization are critical for the engagement of an RHS defect with the posterior glenoid rim. Study design: Controlled laboratory study. Methods: Ten RHS defects with predefined extent and localization were created through an anterolateral rotator cuff sparing approach in 10 fresh-frozen cadaveric shoulder specimens using a custom-made saw guide. Computed tomography scans of all specimens were completed, and standardized measurements were performed to determine the size (alpha angle) and localization (beta angle) of the defect as well as a combination of both parameters (gamma angle). Internal rotation motions were imposed on the shoulder joint in different arm positions and with varying amount of posterior translation by means of a robot-assisted shoulder simulator. The association between engagement of the defects and the defined parameters (alpha, beta, and gamma angles) was analyzed. Results: In 0° of abduction, a cutoff value between engaging and nonengaging defects of 37.5° for the alpha angle (100% sensitivity; 75% specificity; area under the curve [AUC], 0.875; P = .055) and 36.5° for the beta angle (100% sensitivity; 25% specificity; AUC, 0.708; P = .286) was determined. The gamma angle showed the highest discriminatory power (AUC, 0.938; P = .025) with a cutoff value of 85.5° rendering 100% sensitivity and 75% specificity in the prediction of engagement. An increase in the applied posterior translation force decreased the degrees of internal rotation necessary before engagement occurred. No engagement occurred during internal rotation with the arm in 60° of abduction or 60° of flexion. Conclusion: The size and localization of RHS defects are both critical factors for engagement. The combination of both parameters in terms of the gamma angle measurement might be a helpful tool to identify defects prone to engagement. Clinical Relevance: Not only the size but also the localization is decisive for engagement of RHS defects. The standardized measurement of the gamma angle combines both factors and might be a helpful tool to identify defects prone to engagement warranting surgical treatment.